Couples HIV testing and immediate antiretroviral therapy for serodiscordant HIV-positive partners: Translating evidence into programme in Vietnam. (July 2019) - Bui, Duong D; Do, Nhan T; Pham, Linh TT; Nadol, Patrick; Nguyen, Van TT; Dao, Vinh Q; Nguyen, Long H; Duong, Tuan K; Lai, Anh K; Hoang, Chian X; Nguyen, Anh H; Suthar, Amitabh; et al.
Injection drug use and heterosexual transmission from male key populations to their female partners have been the dominant modes of HIV transmission in Vietnam. A demonstration project was conducted to offer immediate antiretroviral therapy (ART) (regardless of CD4 cell count) to HIV-seropositive partners in serodiscordant couples. During March–December 2013, couples HIV testing and counselling (HTC) and immediate ART were offered in two drug use-affected provinces. Of 256 couples receiving couples HTC, 146 (57%) were serodiscordant; 134 (92%) seropositive partners initiated ART irrespective of CD4 cell count. Of these, 86% were male; 57% reported ever using illicit drugs; median CD4 cell count before ART initiation was 374 cells/mm 3 . Consistent condom use was reported by 58, 70 and 71% among HIV-positive partners at months 0, 3 and 12. At 12 months after ART initiation, 119 (89%) HIV-positive partners were retained in care; 96 (95% of those tested) achieved viral suppression (<1000 copies/ml). Uptake of immediate ART and viral suppression among those initiating ART were high, paving the way for ART regardless of CD4 cell count as national policy in Vietnam.